Classroom Action Research: Implementation of the Tartil Method in Learning the Quran - Alfarizi, M.; Mutathahirin, Mutathahirin; Yumna, Yumna; Akmal, Fauzi; Dahliana, Dina; Albizar, Albizar; Taufan, Muhammad; Nova, Febri Sari (UKAZ: International Journal of Islamic Studies, 2024)
The use of appropriate methods is an aspect that influences the success of learning to read the Alquran, the method in question is easy to understand, systematic and appropriate to the diversity of students. This research aims to analyze the impression of using the tartil method in improving students' Alquran reading skills in elementary schools. This research uses quantitative methods with a type of classroom action research through four stages starting from planning, action, observation and reflection. Data sources were taken from fifteen participants through Alquran reading tests and document analysis of student learning outcomes. Apart from that, researchers also collected data through observations at the four stages of the research process carried out. All data was analyzed using SPSS 21 software with descriptive analysis techniques. Research findings from the two cycles of the learning process carried out found that there was an increase in students' ability to read the Alquran after learning using the tartil method. The results of this increase in ability can be seen from the students' final Alquran reading scores in the good (85) and very good (95) categories. Furthermore, the student assessment results sheet also shows satisfactory results with a cumulative learning completeness score above (87) to (96). Referring to the results of this analysis, the use of the tartil method in learning the Alquran has been able to increase students' proficiency in reading the Alquran, in fact, the tartil method can be used as an appropriate method in the process of learning the Alquran.